ONE YEAR DISEASE FREE SURVIVAL IN ACUTE MYELOID LEUKEMIA PATIENTS AFTER INDUCTION REMISSION - Shaikh, Mehwish Roshan; Haider, Ghulam; Shahid, Aisha; Raja Rahool,; Beg, Shumyla; Memon, Paras; Bhunisha,; Nouman, Maryum (Journal of Ayub Medical College Abbottabad, 2021)
Background: Diagnostic karyotyping analysis is routinely used in acute myeloid leukaemia (AML) clinics. Categorization of patients into risk stratified groups (favourable, intermediate and unfavourable) according to cytogenetic findings can serve as a valuable independent prognostic factor. The aim of this study was to assess the one-year disease free survival rate in AML patients after induction remission presenting at tertiary care hospital of Karachi. Methods: It was a longitudinal study conducted at the department of Medical oncology of Jinnah Postgraduate Medical Center, Karachi from Jun 2017-Jan 2019. Ninety-three diagnosed cases of AML of age 15-55 years of either gender were included in the study. All patients received the first cycle of 3+7 regime for induction chemotherapy. This includes Daunorubicin 45 mg/m2 on days 1 to 3 and Cytarabine in a dose of 100 mg/m2 from day 1-7. Marrow response was assessed on the 21th day of induction therapy. If the bone marrow includes lesser than five percent blast cells then it was labelled as complete remission (CR). The patients who achieved CR and normal haematopoiesis were eligible to receive 4 cycles of consolidation therapy with cytarabine 3 mg/m2 every 12 hour on days 1, 3 and 5. Consolidation cycles were monthly administered. All the patients who achieved CR were follow up for the duration of one year for disease free survival. On follow up monthly visits, outcomes were assessed using CBC report and physical examination. Results: After 1 year, out of 72 AML patients, 19 patients remained in complete remission, 5 patients lost to follow up, 3 relapses, 19 showed persistent disease & 28 died during consolidation. According to cytogenetic status, CR was achieved in 6 patients (50%) with favourable cytogenetic, 14 patients (28%) with intermediate cytogenetic and 2 patients (20%) with unfavourable cytogenetic status. The highest median survival time was observed in patients with favourable cytogenetic status as 5.23 months. However, there was no significant difference was observed in survival time with respect to cytogenetic status. Conclusion: The 3+7 regime of Daunorubicin & Cytarabine is effective in inducing induction remission and increases 1 year survival, however chemotherapy related morality rate was high in unfavourable cytogenetic group